Live Attenuated Salmonella enterica Expressing and Releasing Cell-Permeable Bax BH3 Peptide Through the MisL Autotransporter System Elicits Antitumor Activity in a Murine Xenograft Model of Human B Non-hodgkin's Lymphoma - Mateos-Chávez, Armando Alfredo; Muñoz-López, Paola; Becerra-Báez, Elayne Irene; Flores-Martínez, Luis Fernando; Prada-Gracia, Diego; Moreno-Vargas, Liliana Marisol; Baay-Guzmán, Guillermina Juliana; Juárez-Hernández, Uriel; Chávez-Munguía, Bibiana; Cabrera-Muñóz, Lourdes; Luria-Pérez, Rosendo (Frontiers in Immunology, 2019)
The survival of patients with non-Hodgkin's lymphoma (NHL) has substantially improved with current treatments. Nevertheless, the appearance of drug-resistant cancer cells leads to patient relapse. It is therefore necessary to find new antitumor therapies that can completely eradicate transformed cells. Chemotherapy-resistant cancer cells are characterized by the overexpression of members of the anti-apoptotic B-cell lymphoma 2 (Bcl-2) protein family, such as Bcl-XL, Bcl-2, and Mcl-1. We have recently shown that peptides derived from the BH3 domain of the pro-apoptotic Bax protein may antagonize the anti-apoptotic activity of the Bcl-2 family proteins, restore apoptosis, and induce chemosensitization of tumor cells. In this study, we investigated the feasibility of releasing this peptide into the tumor microenvironment using live attenuated Salmonella enterica, which has proven to be an ally in cancer therapy due to its high affinity for tumor tissue, its ability to activate the innate and adaptive antitumor immune responses, and its potential use as a delivery system of heterologous molecules. Thus, we expressed and released the cell-permeable Bax BH3 peptide from the surface of Salmonella enterica serovar Typhimurium SL3261 through the MisL autotransporter system. We demonstrated that this recombinant bacterium significantly decreased the viability and increased the apoptosis of Ramos cells, a human B NHL cell line. Indeed, the intravenous administration of this recombinant Salmonella enterica elicited antitumor activity and extended survival in a xenograft NHL murine model. This antitumor activity was mediated by apoptosis and an inflammatory response. Our approach may represent an eventual alternative to treat relapsing or refractory NHL.